Edukasi Pencegahan Tuberkulosis Berbasis Lingkungan dengan Penerapan PHBS di Desa Teubang Phui Baro Aceh Besar: Pengabdian - Mhd. Hidayattullah; Taufiq Karma; Nasywa Nabila; Arsita Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Tuberculosis (TB) remains a major public health problem in Indonesia, including in Aceh Province, which reported more than 12,000 cases in 2024, most of which were found in rural areas. This situation is exacerbated by the low public awareness of Clean and Healthy Living Behavior (CHLB) and poor environmental hygiene. This community service activity aimed to improve community knowledge, attitudes, and practices related to TB prevention through environment-based CHLB education in Teubang Phui Baro Village, Aceh Besar District. The methods applied included interactive lectures, demonstrations, and participatory discussions involving 50 respondents, with knowledge evaluation conducted through pre-test and post-test assessments. The results showed an increase in the average knowledge score from 55.0 to 86.4, indicating a 31.4% improvement, with TB prevention knowledge rising by 36% and CHLB understanding by 32%. These findings indicate that environment-based education is effective in enhancing community awareness of TB prevention. Similar programs are recommended to be implemented continuously as part of efforts to support the 2030 TB elimination target in Aceh and to strengthen clean and healthy living practices at the community level.